The Influence Of Environmental, Social, And Governance Disclosure, Board Gender Diversity, And Firm Size On Financial Performance - Farel Adira Putra; Putri, Intan Lifinda Ayuning (Reviu Akuntansi, Keuangan, dan Sistem Informasi, 2026)
Previous studies on the relationship between ESG, board gender diversity, firm size, and financial performance still leave many research gaps. Accordingly, this quantitative study examines the influence of environmental, social, and governance (ESG) disclosure, board gender diversity, and firm size on the financial performance of energy companies listed on the Indonesia Stock Exchange (IDX) during 2022-2024. This sector was selected due to its significant contribution to the national economy and substantial environmental and social challenges. Secondary data, including financial statements and sustainability reports, were collected from 84 energy companies selected through purposive sampling. Panel data regression analysis using EViews 12 shows that ESG disclosure and firm size positively and significantly affect financial performance, while board gender diversity does not have a significant effect. These findings underscore the importance of ESG transparency, board gender diversity, and firm size in enhancing legitimacy, accountability, and competitiveness, ultimately driving financial performance.